Літературно-критична діяльність Ю. Лободовського у варшавському часописі «Biuletyn Polsko-Ukrainski» - Жулинська-Яручик, О.; Яручик, В. (Літературознавчі обрії. Праці молодих учених, 2010)
The article presents an analysis of the literary critical activity conducted by one of the well-known Polish writers of the XX century Y. Lobodowski in «Polish-Ukrainian Bulletin». The authors concentrate on the work of Y. Lobodowski in the periodical as the leading literature critic from Polish side. The important role which the «Bulletin» played in the old Polish-Ukrainian relations (the 30’s of the XX century) is stressed in the paper. W rozprawie ukazano analize działalnosci krytyczno-literackiej w «Biuletynie Polsko-Ukrainskim» jednego z najwiekszych polskich pisarzy XX wieku J. Łobodowskiego. Podkreslajac waRna role, która odgrywał «Biuletyn» w ówczesnych stosunkach polsko-ukrainskich (okres lat 30 XX wieku), autorka szczególna uwage kładzie na działaniu J. Łobodowskiego w czasopismie, jako wiodacego krytyka literackiego ze strony polskiej w «Biuletynie Polsko-Ukrainskim».